Illuminating Details: Reflections on a Practice of Anthropology - Dyck, Noel (Anthropologica, 2020)
<span style="color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This revised address for the 2019 Weaver-Tremblay Award revisits some underlying questions about the practice of anthropology that have figured in my own work. First, why might one choose anthropology as a means of intellectual and practical inquiry into social and cultural phenomena? Second, what kinds of anthropological practice can be pursued? Finally, what types of knowledge can be acquired through anthropological approaches, and to what purposes might this knowledge be applied? These questions are considered within the context of two rather different fields of anthropological inquiry I have pursued: relations between Indigenous Peoples and state governments, on the one hand, and the social construction of sport, on the other. As well as sharing some unexpected analytical commonalities, these ostensibly disparate fields speak to the power that resides in illuminating details of the type that anthropologists are particularly adept in recognizing.